2013
DOI: 10.1364/oe.21.018724
|View full text |Cite
|
Sign up to set email alerts
|

20 GHz spacing multi-wavelength generation of Brillouin-Raman fiber laser in a hybrid linear cavity

Abstract: We demonstrate a tunable multi-wavelength Brillouin-Raman fiber laser with 20 GHz wavelength spacing. The setup is arranged in a linear cavity by employing 7.2 and 11 km dispersion compensating fibers (DCF) in addition to a 30 cm Bismuth-oxide erbium doped fiber. In this experiment, for the purpose of increasing the Stokes lines, it is necessary to optimize Raman pump power and Brillouin pump power together with its corresponding wavelengths. At the specific Brillouin pump wavelength, it is found that the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…A combination of SBS and erbium gain can be used to obtain Brillouin comb generation in random fiber lasers [93][94][95][96]. For example, Mamdoohi et al [94] demonstrated a 28 nm span of Brillouin comb interspaced by 20 GHz in a configuration employing a span of DCF fiber, followed by a 30 cm long highly doped bismuth oxide erbium fiber. The erbium fiber was pumped by the undepleted pump from the DCF fiber, which then amplified the resulting Brillouin cascades.…”
Section: Spectral Properties Of Random Fiber Lasers Of Other Typesmentioning
confidence: 99%
“…A combination of SBS and erbium gain can be used to obtain Brillouin comb generation in random fiber lasers [93][94][95][96]. For example, Mamdoohi et al [94] demonstrated a 28 nm span of Brillouin comb interspaced by 20 GHz in a configuration employing a span of DCF fiber, followed by a 30 cm long highly doped bismuth oxide erbium fiber. The erbium fiber was pumped by the undepleted pump from the DCF fiber, which then amplified the resulting Brillouin cascades.…”
Section: Spectral Properties Of Random Fiber Lasers Of Other Typesmentioning
confidence: 99%
“…Other parameters in Eq. (5) that include 0.05ln (10) s s α Γ = is the fiber loss coefficient at the signal wavelength and 0.05ln (10) p p α Γ = is that at the pump wavelength [18]. In the next parameter, / 2…”
Section: Laser Structure and Principle Of Operationmentioning
confidence: 99%
“…However, the implementation of FWM and NPR techniques to initiate multiple wavelengths introduces lower stability, high cost and complexity [4,5]. Alternatively, a better solution is provided when utilizing SBS effects in various gain media [6][7][8][9][10]. Among these technologies, the Brillouin-Raman fiber laser (BRFL) has several advantages and potential applications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations